Illocutionary Acts of Elon Musk at Ted Talk 2022 - Aflah, Ibnu Bisri; Setyawan, Agustinus Hary (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Every utterance produced by a speaker has its own type and function. However, this research focuses on illocutionary speech acts. This research aims to describe the types and functions of illocutionary speech acts in the conversation between Elon Musk and the moderator at TED Talk 2022 and describe the function of these speech acts. This data is in the form of sentences and clauses in conversations between Elon Musk and Chris Anderson which contain illocutionary acts. The data source was collected through observation methods using transcribing and note-taking techniques by watching and listening to video to know the context. The data is analyzed qualitatively using the theory proposed by Searle to study various types of illocutionary acts, followed by the theory proposed by Leech regarding the functions of illocutionary acts. The data analysis method used in this study is constant comparative or often called the equivalent method. The problems in this research are (1) What speech acts are contained in the conversation between Elon Musk and the moderator and (2) What is the function of each utterance. The results show that there are 4 types of speech acts in the conversation between Elon Musk and the moderator, namely (1) Assertive, (2) Directive, (3) Commissive, and (4) Expressive. Based on the function of illocutionary speech, two functions are obtained, namely (1) Collaborative function and (2) Convival function. The researcher suggests that further research needs to be carried out to understand illocutionary acts in conversation to be able to provide information and it is also necessary to pay attention to the context and situation to understand the meaning.